Crossing frontiers between tourism and demography. An empirical analysis based on European travellers’ behaviour - Serra, Jaime (2017)
This paper aims to establish possible tourism demand scenarios of European travellers to Portugal based on the relationship with changing population structures. A combination of the EUROBAROMETER report 370 (“Attitudes of Europeans towards Tourism in 2013”) and the cohort-component method for population projections will allow the development of different possible tourism demand scenarios. Following the European report, individuals who travelled in 2013 were most likely to live in a household with two or more individuals. Thus, if elderly couples are together till later in their life and in better physiological shape, it is possible that the number of elderly individuals travelling for tourism purposes will increase in the near future. If we can expect tourists from developing countries to be younger due to their demographic dynamics than those from developed countries, where the ageing population is growing fast, we can expect that the percentage of the elderly among tourists will increase. Furthermore, the 2013 European report found that the combination of socio-demographic variables, such as, age, population, gender, household dimension, country of residence and trip purpose explained tourism demand scenarios for Portugal, confirming that seniors and families evidence a paramount sense of importance for the destination. In the literature there is a lack of discussion about the effects of demography in the future and the role of an ageing population in tourism demand choice patterns. We aim to contribute to filling this gap. Consequently, we strongly believe that this paper contributes to the literature by introducing a new field of discussion about the importance of demographic changes in shaping travel trends.